2018
DOI: 10.11606/s1518-8787.2018052000252
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with preventable infant death: a multiple logistic regression

Abstract: OBJECTIVETo identify and analyze factors associated with preventable child deaths.METHODSThis analytical cross-sectional study had preventable child mortality as dependent variable. From a population of 34,284 live births, we have selected a systematic sample of 4,402 children who did not die compared to 272 children who died from preventable causes during the period studied. The independent variables were analyzed in four hierarchical blocks: sociodemographic factors, the characteristics of the mother, prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
8
0
11
Order By: Relevance
“…Additional intersectoral actions could also contribute to health promotion and positive outcomes in maternal and child health (33) . Moreover, issues regarding educational level, family income, access to healthcare services, basic sanitation and living conditions also influence outcomes (17,34) . These determinant factors reflect the greater vulnerability of these mothers to situations of risk and influence fetus and infant survival (17,25,34) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional intersectoral actions could also contribute to health promotion and positive outcomes in maternal and child health (33) . Moreover, issues regarding educational level, family income, access to healthcare services, basic sanitation and living conditions also influence outcomes (17,34) . These determinant factors reflect the greater vulnerability of these mothers to situations of risk and influence fetus and infant survival (17,25,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, issues regarding educational level, family income, access to healthcare services, basic sanitation and living conditions also influence outcomes (17,34) . These determinant factors reflect the greater vulnerability of these mothers to situations of risk and influence fetus and infant survival (17,25,34) . In Nigeria, the results of a study analyzing socioeconomic inequalities in infant mortality among groups defined by wealth, maternal educational level and maternal age clearly showed that a significant proportion of infant deaths could have been avoided if socioeconomic inequalities in rates of infant mortality had been eliminated/reduced by appropriate policies (35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of proximal (e.g., health-related factors), intermediate (e.g., water and sanitation), and distal (e.g., education and income) determinants are thought to predict infant and child mortality (Mosley & Chen, 2003). These determinants include breastfeeding (Iram & Butt, 2008;Lamichhane et al, 2017;Reno & Hyder, 2018), baby's birth size and weight (Lamichhane et al, 2017;Memiah et al, 2020;Vidal e Silva et al, 2018), and place and type of delivery (Iram & Butt, 2008;Lamichhane et al, 2017;Memiah et al, 2020). Poor health of newborn (Vidal e Silva et al, 2018), prenatal and postnatal care (Iram & Butt, 2008;Reno & Hyder, 2018), multiple births (Dwomoh et al, 2019;Vidal e Silva et al, 2018), and birth interval (Dwomoh et al, 2019;Lamichhane et al, 2017;Reno & Hyder, 2018) are also found to be associated with infant mortality.…”
Section: Introductionmentioning
confidence: 99%
“…These determinants include breastfeeding (Iram & Butt, 2008;Lamichhane et al, 2017;Reno & Hyder, 2018), baby's birth size and weight (Lamichhane et al, 2017;Memiah et al, 2020;Vidal e Silva et al, 2018), and place and type of delivery (Iram & Butt, 2008;Lamichhane et al, 2017;Memiah et al, 2020). Poor health of newborn (Vidal e Silva et al, 2018), prenatal and postnatal care (Iram & Butt, 2008;Reno & Hyder, 2018), multiple births (Dwomoh et al, 2019;Vidal e Silva et al, 2018), and birth interval (Dwomoh et al, 2019;Lamichhane et al, 2017;Reno & Hyder, 2018) are also found to be associated with infant mortality. Maternal age and health (Iram & Butt, 2008;Reno & Hyder, 2018;Vidal e Silva et al, 2018), maternal substance use (Reno & Hyder, 2018), education (Andriano & Monden, 2019;Dutta et al, 2020;Iram & Butt, 2008;Reno & Hyder, 2018), poor socioeconomic status (Ezeh et al, 2015;Iram & Butt, 2008;Reno & Hyder, 2018), rural residence and region (Ezeh et al, 2015;Lamichhane et al, 2017), area disadvantage (Reno & Hyder, 2018;Vidal e Silva et al, 2018), and female labor participation or employment (Akinyemi et al, 2018;Scharber, 2014) also predicted child and infant mortality.…”
Section: Introductionmentioning
confidence: 99%